THE INFLUENCE OF DIGITAL SKILLS AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE MEDIATED BY ABILITY AT PT. KSB INDONESIA - Lutfiyah Apriliani; Ica Nuranisa; Retno Purwani Setyaningrum (LPPM STIE EKA PRASETYA, 2025)
This study examines the impact of digital skills and career development on employee performance with ability as a mediator at PT KSB Indonesia. Using a non-probability simple random sampling method, 86 respondents were surveyed. The research utilized the Partial Least Squares (PLS) method (SmartPLS 3.0 software) for data analysis. The results indicate that digital skills and career development significantly improve employee performance and ability. Furthermore, ability mediates the relationship between digital skills, career development, and employee performance, strengthening the overall impact. This study highlights the importance of designing effective digital skills and career development programs to enhance employee performance at PT KSB Indonesia.